Can ring current stabilize magnetotail during steady magnetospheric convection?. Issue 12 (29th December 2015) - Dubyagin, S.; Ganushkina, N.; Liemohn, M.; Kubyshkina, M.
Abstract: The present study investigates the role of the ring current in stabilizing the magnetotail during steady magnetospheric convection (SMC) events. We develop a method for estimation of the symmetric ring current intensity from the single spacecraft magnetic field observations. The method is applied to a large number of SMC events identified using three different automatic procedures adopted from the literature. It is found that the symmetric ring current can be weak or strong depending on a particular event. We find a significant fraction of events that have a rather weak symmetric ring current in spite of the strong solar wind driving during the event. These findings imply that the symmetric ring current plays no role in the magnetotail stabilization. Key Points: Analysis of AE‐based criteria for SMC selection New method for ring current intensity estimation Ring current plays no role in magnetotail stabilization